Vefeyâtü'l-a'yân ve enbâu ebnâi'z-zamân ; eş-Şakaiku'n-Nu'mâniyye fî ulemâi'd-Devleti'l-Osmaniyye ; el-İkdu'l-manzûm fî zikri efazili'r-Rûm - İbn Hallikân, 1211-1282. (Bulak [Mısır])
2. c. (10, 563 s.)